2016
DOI: 10.1111/medu.13080
|View full text |Cite
|
Sign up to set email alerts
|

Number needed to eat: pizza and resident conference attendance

Abstract: The didactic conference is a common part of the resident education curriculum. Given the demands of clinical responsibilities and restrictions on duty hours, maximising education is a challenge faced by all residency programmes. To date, little research exists with respect to how the provision of complimentary food affects physician and resident conference attendance. The objective of this study was to determine whether complimentary food improves resident arrival times and attendance at educational conference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This study sought to identify the barriers and facilitators to attending and presenting at Evidence Rounds. Our findings agreed with evidence from other studies that the provision of refreshments may be associated with increased HCP attendance at educational events [30, 31].…”
Section: Discussionsupporting
confidence: 93%
“…This study sought to identify the barriers and facilitators to attending and presenting at Evidence Rounds. Our findings agreed with evidence from other studies that the provision of refreshments may be associated with increased HCP attendance at educational events [30, 31].…”
Section: Discussionsupporting
confidence: 93%
“…Even with the provision of food in one example, resident noon conferences were attended, on average, by only 35% of the residents over two years. 2 Lecture attendees frequently cycle between episodes of attention and in-attention, 3 disagree with the faculty on the ideal content, [4][5] and their learning outcomes may not improve, especially when compared to active learning strategies. [6][7] Taken together, resident learning activities should be reformed to better meet trainees' needs, accommodate their fluid schedules, maintain their attention, and promote knowledge retention.…”
Section: Introductionmentioning
confidence: 99%
“… 63 , 79 One pediatric residency program reported that providing lunch with noon conferences was associated with statistically significant improvements in attendance and punctuality. 48 …”
Section: Resultsmentioning
confidence: 99%